(untitled) - Bairoch, Paul (Chicago, 1988)
Translation of: De Jéricho à Mexico; Includes bibliography and index
Keywords: Cities and towns -- Growth -- History; Economic development -- History; Urban economics -- History; Urbanization -- History; Thành phố và thị trấn -- Phát triển -- Lịch sử; Phát triển kinh tế -- Lịch sử; Kinh tế đô thị -- Lịch sử; Đô thị hóa -- Lịch sử